Lasso loop technique using bioabsorbable thread to treat intra-articular distal radius fracture. Issue 47 (24th November 2021) - Kaji, Yoshio; Yamaguchi, Konosuke; Nomura, Yumi; Oka, Kunihiko; Shimamura, Masashi; Kawakami, Shohei; Yamamoto, Tetsuji
Abstract : Abstract: This article introduces our lasso loop technique (LLT) using a bioabsorbable thread for the treatment of intra-articular distal radius fractures with displaced dorsal bone fragment containing articular surface (DBF). We also examined whether the articular gap is sufficiently reduced and maintained by the LLT, along with the results of other radiological and clinical evaluations. We retrospectively reviewed 19 patients who underwent LLT for intra-articular distal radius fracture with a displaced DBF. Patient radiographic images and medical records were used to investigate radiological characteristics, symptoms, physical findings, and the Quick Disabilities of the Arm, Shoulder, and Hand scores. Sagittal-view computed tomography showed that the mean preoperative articular gap was 2.6 mm, but the gap was reduced by LLT, and the gap immediately postoperatively was <1.0 mm in all patients. No re-displacement of the DBF was evident from immediately postoperatively to 6 months postoperatively. Postoperatively, no losses of correction in palmar tilt, radial inclination, or ulnar variance were seen in the evaluation of plain radiographs, and satisfactory joint range of motion, grip strength, and the Quick Disabilities of the Arm, Shoulder, and Hand score were obtained. No significant complications due to LLT were observed. LLT appears to offer a simple and effective procedure to reduce displaced DBF with little risk of complications. LLT may become a useful option in the treatment of intra-articular distal radius fractures with displaced DBF.